Practice of Healthcare Workers during the COVID-19 pandemic at the Emergency Department of Nepal - Chaudhary, Ritesh; Bhandari, Rabin; Poudel, Masum; Giri, Rajani; Yadav, Ajay Kumar; Aryal, Bijaya Devi (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: The study intends to explore the effects and practice of healthcare workers during COVID-19 pandemic at the emergency department of B. P. Koirala Institute of Health Sciences. Methods: A cross-sectional study was done among the healthcare workers of the Emergency Department of B. P. Koirala Institute of Health Sciences from August 2020 to Jan 2021. Data were collected by using a semi-structured interview among all the participants in the survey. A convenient sampling method was used and analysed using descriptive statistics. A p value < 0.05 was considered statistically significant. Results: Majority of the healthcare workers (90%) stated that their role has increased during COVID 19 first wave pandemic. A similar percentage (71%) noticed change in their duty hours and subsequently Isolation/ Quarantine. More than half (53%) stated that efforts been undertaken to bring additional health care workers to emergency department on basis of safety and preservation of workforce. The institute was able to train (47%) health care workers regarding proper handling of personal protective equipment despite of its insufficient (70%) supply. Conclusion: The results take exceptions in the emergency department despite insufficient supply of personal protective equipment, longtime exposure to large numbers of infected patients and insufficient care to quarantine a majority of the healthcare workers during COVID-19 pandemic.